Pengaruh Strategi Pemasaran Jasa Pendidikan Terhadap Kepuasan Pelayanan Bagi Peserta Didik di SMP IT Mutiara Hikmah Bekasi - Fauziah, Evi Hopipah; Nurlaeli, Acep; Ma'shum, Sya'roni (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2024)
This research was conducted to find out whether students were satisfied with what was promised when the PPDB committee carried out its marketing with the services available at the Mutiara Hikmah IT Middle School Bekasi because seen from the condition of the number of interested students at Mutiara Himah IT Middle School from year to year, sometimes it was in accordance with the quota. or less than the quota that has been set, while the strategy carried out has been maximized to attract the interest of prospective new students. This research uses a quantitative research approach and correlational methods. The population in this study involved grades VII to IX, with a sample of 73 students. Data collection techniques using questionnaires and documentation. For data analysis used, namely descriptive statistics and classical assumption tests, hypotheses were tested by calculating the coefficient of determination, significance level, and regression analysis. The results of the research show that there is an influence of educational service marketing strategies on service satisfaction for students. It is known that the calculated t value is 12.976 > 1.993 t table with a significance value of 0.000 < 0.05, which means that Ho is rejected and Ha is accepted. The level of influence of educational service marketing strategies on the service satisfaction variable for students is 70.3% with the remaining 29.7% being influenced by variables not studied. Keywords: Marketing, Education and Service Satisfaction